Feed restriction and a diet's caloric value: The influence on the aerobic and anaerobic capacity of rats - de Moura, Leandro Pereira [UNESP]; Kalva-Filho, Carlos Augusto [UNESP]; Loures, Joao Paulo [UNESP]; Silva, Maria de Sousa [UNESP]; Zorzetto, Lucas Pilla [UNESP]; Costa Junior, Marcelo [UNESP]; de Araujo, Michel Barbosa [UNESP]; Dalia, Rodrigo Augusto [UNESP]; Rostom de Mello, Maria Alice [UNESP] (Biomed Central Ltd., 2012)
Background: The influence of feed restriction and different diet's caloric value on the aerobic and anaerobic capacity is unclear in the literature. Thus, the objectives of this study were to determine the possible influences of two diets with different caloric values and the influence of feed restriction on the aerobic (anaerobic threshold: AT) and anaerobic (time to exhaustion: Tlim) variables measured by a lactate minimum test (LM) in rats.Methods: We used 40 adult Wistar rats. The animals were divided into four groups: ad libitum commercial Purina (R) diet (3028.0 Kcal/kg) (ALP), restricted commercial Purina (R) diet (RAP), ad libitum semi-purified AIN-93 diet (3802.7 Kcal/kg) (ALD) and restricted semi-purified AIN-93 diet (RAD). The animals performed LM at the end of the experiment, 48 h before euthanasia. Comparisons between groups were performed by analysis of variance (p < 0,05).Results: At the end of the experiment, the weights of the rats in the groups with the restricted diets were significantly lower than those in the groups with ad libitum diet intakes. In addition, the ALD group had higher amounts of adipose tissue. With respect to energetic substrates, the groups subjected to diet restriction had significantly higher levels of liver and muscle glycogen. There were no differences between the groups with respect to AT; however, the ALD group had lower lactatemia at the AT intensity and higher Tlim than the other groups.Conclusions: We conclude that dietary restriction induces changes in energetic substrates and that ad libitum intake of a semi-purified AIN-93 diet results in an increase in adipose tissue, likely reducing the density of the animals in water and favouring their performance during the swimming exercises.
Keywords: Diet; Feed restriction; Lactate minimum